2013
DOI: 10.1590/s0034-71672013000600004
|View full text |Cite
|
Sign up to set email alerts
|

Práticas da equipe de enfermagem no processo de alta do bebê pré-termo

Abstract: The objective of this study was to identify the strategies used by the nursing team in the neonatal unity care of a school-hospital during the preparation of the family for the premature baby discharge. It is a descriptive study with qualitative approach. The data was collected between March and June 2011, by means of observation and semi-structured interviews. From the discourse analysis two categories appeared: Orientations and professional strategies in preparing the family for the premature baby hospital d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 11 publications
1
22
0
10
Order By: Relevance
“…In the case of hospitalization of the child in the NICU, this contact is compromised, and many doubts about the child's survival are often associated with feelings of incapacity, guilt and fear. 27 The hospitalization in the NICU inserts the NB in an inhospitable atmosphere where the exposure to stress and pain is common due to complex therapies. It is found that, at the bedside, mothers are frightened and curious when they observe the physical environment full of apparatuses and sounds, perhaps unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of hospitalization of the child in the NICU, this contact is compromised, and many doubts about the child's survival are often associated with feelings of incapacity, guilt and fear. 27 The hospitalization in the NICU inserts the NB in an inhospitable atmosphere where the exposure to stress and pain is common due to complex therapies. It is found that, at the bedside, mothers are frightened and curious when they observe the physical environment full of apparatuses and sounds, perhaps unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Even mothers with other children associate prematurity with fragility of the baby, which triggers the need for specific and differentiated care; such care is possible by the extension of professional support at home. (14) To reduce these situations, guidance on particularities of extremely low birth weight babies was given. The assistance might be provided in a conventional manner that respected the context of the baby's family and cultural practices.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, tem se estabelecido como um processo continuo que se inicia desde a internação da criança prematura na UTIN (14), que inclui o ensino estruturado e o ensino informal (15). O conceito desde a perspectiva da enfermagem, não é exclusivo do cuidado neonatal.…”
Section: Definição E Uso Do Conceito: Preparo Para a Alta Da Unidade Neonatalunclassified